2008
DOI: 10.1245/s10434-008-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Sparing Mastectomy: Critical Assessment of 51 Procedures and Implications for Selection Criteria

Abstract: Using careful patient selection and careful pathological evaluation of the subareolar breast tissue at surgery, NSM can be an oncologically safe procedure in patients where this is important to their quality of life. A prospective study based on focused selection criteria and long-term follow-up is currently in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 26 publications
6
71
0
8
Order By: Relevance
“…In general, NSM is considered for patients with T0 to T2 tumours smaller than 4.5 cm in size, further than 2.5 cm from the areolar edge and 4 cm from the nipple centre, and no clinical involvement of the nipple-areolar complex (NAC) or skin (5). Recent studies, however, report that NSM can be used in all cases in which total mastectomy is indicated when histological analyses of intraoperative frozen sections from sub-NAC tissues are negative (6).…”
mentioning
confidence: 99%
“…In general, NSM is considered for patients with T0 to T2 tumours smaller than 4.5 cm in size, further than 2.5 cm from the areolar edge and 4 cm from the nipple centre, and no clinical involvement of the nipple-areolar complex (NAC) or skin (5). Recent studies, however, report that NSM can be used in all cases in which total mastectomy is indicated when histological analyses of intraoperative frozen sections from sub-NAC tissues are negative (6).…”
mentioning
confidence: 99%
“…In the study by Rulli et al, the decision for adjuvant RT was based on the remaining breast tissue, with residual glandular tissue as an indication for RT (n=10) and no remaining tissue after NSM as an indication for withholding RT (n=50) (18). Only one study group found a significant difference in locoregional recurrence rate depending on the application of RT, as determined in 216 patients (8.5% with RT vs. 28.4% without RT) (12). The tumor stage contributions in the two groups were not supplied.…”
Section: Adjuvant Rtmentioning
confidence: 93%
“…According to the reviewed literature, NSM appears a feasible option without an increased risk of locoregional recurrences for selected patients with invasive breast cancer and/or DCIS (12)(13)(14)(15)(16)(19)(20)(21)(22)(23)(24)39,40). Including a wide range of tumor (T) and node (N) stages, and tumor distances from the NAC, the overall NAC recurrence rates were low, ranging from 0-3.7% (Table I).…”
Section: Disease Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported rate of nipple necrosis is quite low (approximately ≤1%) (91). Despite these and other studies (92,93) reporting promising results with nipple-sparing mastectomy, there are currently no randomized controlled trial data on the oncological safety of nipplesparing compared with conventional skin-sparing mastectomy. Therefore, nipple-sparing mastectomy is generally not recommended for patients with malignancy (21,24,27).…”
Section: What Is the Appropriate Extent Of Mastectomy?mentioning
confidence: 97%